Thioredoxin Reductase 1 Is a Highly Immunogenic Cell Surface Antigen in Paracoccidioides spp., Candida albicans, and Cryptococcus neoformans - de Oliveira, Fabiana Freire Mendes; Paredes, Verenice; de Sousa, Herdson Renney; D’Áurea Moura, Ágata Nogueira; Riasco-Palacios, Juan; Casadevall, Arturo; Felipe, Maria Sueli Soares; Nicola, André Moraes (Frontiers in Microbiology, 2020)
The increasing number of immunocompromised people has made invasive fungal infections more common. The antifungal armamentarium, in contrast, is limited to a few classes of drugs, with frequent toxicity and low efficacy pointing to the need for new agents. Antibodies are great candidates for novel antifungals, as their specificity can result in lower toxicity. Additionally, the immunomodulatory activity of antibodies could treat the underlying cause of many invasive mycoses, immune disfunction. In a previous comparative genomics study, we identified several potential targets for novel antifungals. Here we validate one of these targets, thioredoxin reductase (TRR1), to produce antibodies that could be useful therapeutic tools. Recombinant TRR1 proteins were produced by heterologous expression in Escherichia coli of genes encoding the proteins from Candida albicans, Cryptococcus neoformans and Paracoccidioides lutzii. These proteins were then used to immunize mice, followed by detection of serum antibodies against them by ELISA and western blot. A first set of experiments in which individual mice were immunized repeatedly with TRR1 from a single species showed that all three were highly immunogenic, inducing mostly IgG1 antibodies, and that antibodies produced against one species cross-reacted with the others. In a second experiment, individual mice were immunized three times, each with the protein from a different species. The high titers of antibodies confirmed the presence of antigenic epitopes that were conserved in fungi but absent in humans. Immunofluorescence with sera from these immunized mice detected the protein in the cytoplasm and on the cell surface of fungi from all three species. These results validate TRR1 as a good target for potentially broad-spectrum antifungal antibodies.